At a glance neonatologi / Tom Lissauer dan Avroy A. Fanaroff ; alih bahasa, Vidhia Umami ; editor, Amalia Safitri. - LISSAUER, Tom; Fanaroff, Avroy A.; Vidhia Umami; Amalia Safitri (Erlangga, 2009)
192 hlm. : ilus. ; 28 cm (3 eks.)